Limbostomy: Longitudinal Intravital Microendoscopy in Murine Osteotomies. Issue 5 (20th March 2020) - Stefanowski, Jonathan; Fiedler, Alexander F.; Köhler, Markus; Günther, Robert; Liublin, Wjatscheslaw; Tschaikner, Martin; Rauch, Ariana; Reismann, David; Matthys, Romano; Nützi, Reto; Bixel, Maria Gabriele; Adams, Ralf H.; et al.
Abstract: Bone healing involves the interplay of immune cells, mesenchymal cells, and vasculature over the time course of regeneration. Approaches to quantify the spatiotemporal aspects of bone healing at cellular resolution during long bone healing do not yet exist. Here, a novel technique termed Limbostomy is presented, which combines intravital microendoscopy with an osteotomy. This design allows a modular combination of an internal fixator plate with a gradient refractive index (GRIN) lens at various depths in the bone marrow and can be combined with a surgical osteotomy procedure. The field of view (FOV) covers a significant area of the fracture gap and allows monitoring cellular processes in vivo . The GRIN lens causes intrinsic optical aberrations which have to be corrected. The optical system was characterized and a postprocessing algorithm was developed. It corrects for wave front aberration‐induced image plane deformation and for background and noise signals, enabling us to observe subcellular processes. Exemplarily, we quantitatively and qualitatively analyze angiogenesis in bone regeneration. We make use of a transgenic reporter mouse strain with nucleargreen fluorescent protein and membrane‐bound tdTomato under the Cadherin‐5 promoter. We observe two phases of vascularization. First, rapid vessel sprouting pervades the FOV within 3–4 days after osteotomy. Second, the vessel network continues to be dynamically remodeled until the end of our observation time, 14 days after surgery. Limbostomy opens a unique set of opportunities and allows further insight on spatiotemporal aspects of bone marrow biology, for example, hematopoiesis, analysis of cellular niches, immunological memory, and vascularization in the bone marrow during health and disease. © 2020 The Authors. Cytometry Part A published by Wiley Periodicals, Inc. on behalf of International Society for Advancement of Cytometry.